2016
DOI: 10.4300/jgme-d-15-00106.1
|View full text |Cite
|
Sign up to set email alerts
|

Rounds Today: A Qualitative Study of Internal Medicine and Pediatrics Resident Perceptions

Abstract: Background Attending rounds is a key component of patient care and education at teaching hospitals, yet there is an absence of studies addressing trainees' perceptions of rounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…1,11 The themes are similar to the findings of resident focus groups done at these same sites. 7 Our results support that both medical students and attendings identify the importance of medical education during rounds. This is in contrast with findings in previous observational time-motion research by Stickrath that describes the focus on patient care related activities and the relative scarcity of education during rounds.…”
Section: Discussionsupporting
confidence: 76%
“…1,11 The themes are similar to the findings of resident focus groups done at these same sites. 7 Our results support that both medical students and attendings identify the importance of medical education during rounds. This is in contrast with findings in previous observational time-motion research by Stickrath that describes the focus on patient care related activities and the relative scarcity of education during rounds.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to the present report, a number of prior articles (many cited by Rabinowitz et al 2 ) demonstrated that the chiefs of service, hospital finance officials, and even the individual attending physicians who carry out rounds at teaching hospitals attach very different, sometimes contrary meanings to the term ''attending rounds.'' Humpty Dumpty warned us of the treacherous malleability of language when he said, ''You see it's like a portmanteau-there are two meanings packed up into one word.''…”
mentioning
confidence: 55%
“…4 Furthermore, delivering bad news during BSR, or discussing sensitive topics such as substance use, psychiatric illness, or concerns of malingering behavior, may be difficult and uncomfortable. 4,5 Additionally, some potential diagnoses, such as cancer or human immunodeficiency virus, even if unlikely, could induce panic among patients when they hear them being discussed. 5 Trainees may also lose situational awareness because they focus on the agenda of bedside rounds and fail to respond to patients' emotional needs.…”
Section: Why You Might Think Card Flipping Is Helpfulmentioning
confidence: 99%
“…4,5 Additionally, some potential diagnoses, such as cancer or human immunodeficiency virus, even if unlikely, could induce panic among patients when they hear them being discussed. 5 Trainees may also lose situational awareness because they focus on the agenda of bedside rounds and fail to respond to patients' emotional needs. 6 Efficiency is another reason to avoid BSR.…”
Section: Why You Might Think Card Flipping Is Helpfulmentioning
confidence: 99%